Personality traits, perceived service quality, customer satisfaction and customer loyalty in Penang Hotel Industry - Yap, Gay Soon (2018)
Customer loyalty is an important factor to enable the business to grow and competitiveness enhancement in the current world. The mushrooming number of the hotel had driving hotel service provider competing with each other. Especially, the occupancy rate of the hotel only achieves around 60% to 70% in Malaysia. Customer loyalty is an important factor to secure and increase revenue for the business. The purpose of this research is to examine the relationship between customer personality trait, perceived service quality, customer satisfaction and customer loyalty in the hotel industry. In precise, customer personality traits, perceived service quality, customer satisfaction were used as the measurement tool to analyse the relationship and impact customer loyalty. This data for this research was collected through survey method with 30 items of questionnaires. Total of 389 respondents included in this research was randomly selected using convenient sampling technique among hotel customers in Penang area. The study used SPSS version 22.0 to analyze the data. The findings indicate that personality trait of openness to experience, extra version and neuroticism does not have positive relationship and impact customer loyalty, whereby conscientiousness and agreeableness are positive relationship and impact customer loyalty. Meanwhile, perceived service quality and customer satisfaction are positive relationship and impact customer loyalty. The results of this study can be used by a hotel or other management to perform better in relation. The findings extend the researcher's understanding of predictors such as personality traits, perceived service quality and customer satisfaction that influence customer loyalty among hotel service providers in Malaysia